2016
DOI: 10.1371/journal.pone.0166850
|View full text |Cite
|
Sign up to set email alerts
|

An Alteration in the Cecal Microbiota Composition by Feeding of 1-Kestose Results in a Marked Increase in the Cecal Butyrate Content in Rats

Abstract: Functional food ingredients, including prebiotics, have been ardently developed for improving the intestinal environment. Fructooligosaccarides (FOS), including fructans, are the well researched and commercialized prebiotics. However, to our knowledge, few studies have been conducted on the physiological effects of each component of FOS as prebiotics. 1-Kestose, a component of FOS, is composed of one glucose and two fructose molecules, and is considered as a key prebiotic component in short-chain FOS. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 34 publications
6
48
0
Order By: Relevance
“…The bifidogenic activity was significantly stronger with 1-kestose than nystose and FOSs in vitro [5]. In our previous study, we demonstrated that 1-kestose showed a dose-dependent relationship with bifidogenic activity in rats [6]. Since 1-kestose naturally occurs in several foods, such as banana, peach, artichoke, onion, barley and wheat [3], and only trace levels of 1-kesotse are consumed in the regular diet, its ability to exert prebiotic effects has drawn attention to its use as a supplement to a regular diet.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…The bifidogenic activity was significantly stronger with 1-kestose than nystose and FOSs in vitro [5]. In our previous study, we demonstrated that 1-kestose showed a dose-dependent relationship with bifidogenic activity in rats [6]. Since 1-kestose naturally occurs in several foods, such as banana, peach, artichoke, onion, barley and wheat [3], and only trace levels of 1-kesotse are consumed in the regular diet, its ability to exert prebiotic effects has drawn attention to its use as a supplement to a regular diet.…”
Section: Introductionmentioning
confidence: 79%
“…The pellet form AIN-93G diet and the AIN-93G-based experimental diets were purchased from CLEA Japan (Tokyo, Japan). Equivalent amount of sucrose (0.1%, 0.2% or 0.3%) in AIN-93G were replaced with 1-kestose in the experimental diets ( Supplementary Table S1) [6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…by traditional cell counting on agar plate other than qPCR amplification [3]. It is obvious the citation is incorrect.Then, we found the above primers in another paper, which came from the same research group, in which a similar experiment was conducted investigating the effect of 1-kestose within a range of 0.5-5.0% [4]. In this paper, the primers have the same sequences but different names (Bif LM26F/Bif 228R).…”
mentioning
confidence: 99%